Predicting complications with pretreatment testing in infantile haemangioma treated with oral propranolol. Issue 7 (26th October 2015) - Tang, Lilian YH; Hing, Jeremy WG; Tang, Jasmine YM; Nishikawa, Hiroshi; Shahidullah, Hossain; Browne, Fiona; Chikermane, Ashish; Parulekar, Manoj
Abstract : Background: Since 2008, orally administered propranolol has rapidly gained acceptance as the preferred therapy for haemangiomas, and is usually initiated by ophthalmologists, dermatologists or plastic surgeons who do not routinely use propranolol for any other indication. During the initial years when experience was limited, most healthcare professionals justifiably adopted a cautious approach when initiating and monitoring treatment. A consensus recommendation from the American Society of Dermatologists suggests routine observation, monitoring and cardiology assessments prior to propranolol initiation. Aim: This study aims to analyse treatment initiation in a large tertiary children's hospital and investigate the value of pretreatment testing in predicting commonly seen adverse reactions of propranolol. Method: 104 eligible patients treated between January 2009 and July 2012 were included. All patients underwent pretesting either with protocol A (administration of test dose with routine observations) or protocol B (cardiology clinic assessment, including two-dimensional echocardiography without test dose). Results: 38.5% (40/104) of patients developed adverse reactions during treatment; however, there were no severe or life-threatening reactions. Protocol A has a sensitivity of 0 (95% CI 0 to 0.17) and specificity of 0.95 (95% CI 0.83 to 0.99). Protocol B has a sensitivity of 0.07 (95% CI 0 to 0.34) and specificity of 0.86 (95% CI 0.63 to 0.96). Conclusions: The predictive values of both protocols for the commonly observed adverse reactions are low. In this series, there is no evidence to suggest that routine pretreatment testing before propranolol initiation is of any value in otherwise healthy children.